INFLUENCE OF MODERN FINANCIAL TECHNOLOGIES ON THE EFFICIENCY OF THE BANKING SECTOR OF UZBEKISTAN - Bekhzod Yusupov (Uzbekistan Open Conference, 2025)
The article analyzes modern trends in financial technology (fintech), the implementation of digital solutions in the banking sector of Uzbekistan and their impact on service accessibility and banking efficiency. It provides examples of digital transformation in local banks and startups, discusses issues such as cyber security, regulation, personnel shortage and digital literacy, and evaluates governmental and private initiatives. Uzbekistan, supported by its young population and state programs (“Digital Uzbekistan – 2030”, Banking Strategy-2025), is rapidly developing in the field of financial digitalization, yet requires continued cooperation between state and private sectors.
Keywords: fintech; banking sector of Uzbekistan; digital transformation; internet banking; mobile banking; artificial intelligence; big data; cyber security; state regulation; service accessibility